How do schoolchildren perceive litter? Overlooked in urban but not in natural environments. (June 2022) - De Veer, Diamela; Drouin, Anthony; Fischer, Jil; González, Camila; Holtmann, Geraldine; Honorato-Zimmer, Daniela; Leyton, Ailin; Núñez, Paloma; Sepúlveda, José Miguel; Vásquez, Nelson; Thiel, Martin
Abstract: Anthropogenic litter is found in all environments, but perceptions of people about this problem depend on the context. We examined the cognition and perception of litter in the environment by schoolchildren from the Pacific Coast of Latin America. Two studies were conducted, (1) in a daily urban context, and (2) on a natural beach; schoolchildren prepared hand-drawn representations of the environment that were evaluated for the presence and perception of litter. Litter cognition was low in urban (<6% of hand-drawn maps with litter) but high in natural environments (>32% of beach drawings with litter). Perception of litter was highly negative in both environments, but information from previous studies suggests that the reasons differ between urban (litter as an indicator of neglect) and natural environments (impact on personal and animal well-being). Our findings indicate the phenomenon of "litter blindness" in urban contexts, which might be an obstacle to effective litter prevention. Highlights: Cognition and perception of anthropogenic litter by schoolchildren was examined. Hand-drawn maps of urban environments had almost no litter. Drawings of natural beach environments had many litter items. Litter items were perceived negatively in both environments. Our findings suggest the phenomenon of "litter blindness" in urban contexts.